HYPHOMYCETE LECANICILLIUM LECANII FOR PLANT PROTECTION FROM SUCKING PESTS AND PHYTOPATHOGENS UNDER GREENHOUSE CONDITIONS - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii)
The hyphomycete Lecanicillium lecanii CNMN-FE-03 (2T20) exhibits high insecticidal activity against melon aphids and acaricidal activity against common spider mites in greenhouse conditions. The mortality rate of melon aphids on the 12th day at a working suspension concentration of 2×106 spores/ml was 87,1%, and at a concentration of 1×107 spores/ml – 91,1%. Acaricidal activity on the 12th day at a working suspension concentration of 2×106 spores/ml was 86,7%, at a concentration of 1×107 spores/ml – 92,8%. The hyphomycete exhibits fungicidal activity against a wide range of pathogens of fungal plant diseases. Sterile zones of 5-16 mm were formed in a dual culture with pathogens on an agar nutrient medium. The strain can be used for biological product manufacturing in order to protect plants from sucking pests and a complex of phytopathogens in a greenhouse. Keywords: hyphomycete, strain, insecticidal, acaricidal, fungicidal activity, Lecanicillium lecanii.